Comprehension assessment method for attribute distinction among objects - Yuen, Matthew Ming Shen (Nanyang Technological University, 2023)
The investigation of Situational Awareness (SA) of Air Traffic Control Officers (ATCOs) is a popular field in Air traffic Management (ATM) research where the dynamic and demanding environment requires the maintenance of high levels of SA. Most studies in this field investigate the effects of increasing workload or the increase of automation dependency on SA in the ATC context. Much research has also been done on finding links between physiological methods to the measure of SA. However, there are less research done to investigate how the criticality of information presented to or obtained by an individual affects his/her ability in gaining situational awareness.